Numerical analysis of temperature distribution enhancement in conical and annular diffusers fitted with swirl generators / Ehan Sabah Shukri - Shukri, Ehan Sabah (Institute of Graduate Studies, UiTM, 2016)
Diffusers are essential components for turbo machines aircraft inlets, combustion chambers, etc. They serve as a converter of the flow dynamic head to static pressure. This is achieved by small angle divergent walls. In combustion chamber, good mixing is essential for high burning rate. The attainment of a satisfying temperature distribution in the exhaust gases is very dependent on the degree of the combustion mixing. As long as temperature distribution enhancement has an important role to achieve good mixing, different enhancement methods have been developed by introducing a secondary flow and increasing of turbulence intensity. Swirl flow generator is one of the essential methods that are utilized to enhance the distribution rate. It can be produced by swirl generators such as helical screwtapes, twist tapes, dimples, fins, struts etc. These generators create turbulent flow and swirling motion that can force the fluid to move in the direction of the flow and in the radial tangential direction. Helical screw-tape and twisted tape insert are an active area for the researchers to study their effects; hence they increase the turbulence intensity and have a dominant role in enhancing heat transfer and temperature distribution. In this research study, a numerical simulation analyses were undertaken in two different types of diffusers; one was a conical diffuser and one was an annular diffuser to enhance heat transfer rate by enhancing temperature distribution in a turbulent flow with air as the working fluid…